2014
DOI: 10.1016/j.ijscr.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular extension of papillary thyroid carcinoma to the internal jugular vein: A case report

Abstract: INTRODUCTIONPapillary thyroid cancer (PTC) is the most common thyroid malignancy and usually spreads via lymphatic system. PTC can sometimes show microscopic vascular invasion, but rarely causes tumour thrombus in the internal jugular vein (IJV) or other great veins of the neck.PRESENTATION OF CASEWe report a case of a 62-year-old female presented with symptomatic central neck mass. Clinical examination revealed a hard solitary right-sided thyroid nodule with ipsilateral cervical lymphadenopathy. Ultrasonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In 1879, Kaufmann and Graham reported the first two cases of vascular tumor thrombus associated with thyroid cancer [4]. It has been generally accepted that patients with malignancies with vascular invasion have poor prognoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1879, Kaufmann and Graham reported the first two cases of vascular tumor thrombus associated with thyroid cancer [4]. It has been generally accepted that patients with malignancies with vascular invasion have poor prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the management of venous tumor thrombus of thyroid cancer, no guidelines have been established yet (including Japanese thyroid tumor guidelines) [4]. Surgical resection or thrombectomy for tumor thrombi in the internal jugular vein has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cases receiving only palliative treatment due to difficult surgical approach resulted in poor outcome [3,17]. There are no standard guidelines available in the literature to manage this condition [18], though there are anecdotal case reports of successful surgical treatment of this condition. Yamagami et al [8] reported a case of successful surgical resection of thyroid cancer with extensive tumor thrombus in the RA.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 The first reported cases of thyroid cancer tumour thrombus was by Kaufmann and Graham in 1879. 5 Most often, tumour thrombus by thyroid carcinoma is asymptomatic, 6 and may not be detected by clinical examination, not being palpable. 1 Imaging plays a vital role in patient assessment and diagnosis.…”
Section: Introductionmentioning
confidence: 99%